Posterior Mediastinal Ganglioneuroma Identified After Investigation of Persistent Cough in a Child: A Case Report - Ferrás, Giulia; Limeira Tenório de Albuquerque, André; Antunes, Paulo Eduardo Hernandes (Brazilian Journal of Case Reports, 2025)
Ganglioneuroma (GN) is a neuroblastic tumor originating from neural crest cells. These tumors are rare, benign, and often asymptomatic, presenting symptoms primarily when adjacent structures are compressed. In this report, the authors describe a case of persistent cough in a three-year-old boy with an extensive thoracic mass, ultimately diagnosed as a posterior mediastinal ganglioneuroma, emphasizing the key aspects involved in diagnosing this condition. This case highlights the importance of imaging evaluation in refractory pediatric respiratory symptoms and underscores the need to include neuroblastic tumors in the differential diagnosis.